THE INTERRELATION BETWEEN VALUE ORIENTATIONS AND MOTIVES OF CONSUMER BEHAVIOR OF YOUTH - Sargsyan , L.S. (Modern Psychology, 2019)
The study examined the relationship between personal value orientations and motives of consumer behavior among Armenian youth. The results of correlation analysis show that consumption motives of growth correlate with value orientations of openness to change and with self-enhancement values. On the other hand, consumption motives of preservation correlate with conservation and self-transcendence value orientations. These results indicate about strong interrelation between personal value orientations and consumption motives as a same base for consumer behavior.
Keywords: consumption, consumer behavior, consumer motives, value orientations.